Interleukin-1 receptor antagonist production in cultured synovial cells from patients with rheumatoid arthritis and osteoarthritis. Issue 4 (April 1995) - Fujikawa, Y; Shingu, M; Torisu, T; Masumi, S
Abstract : OBJECTIVE--To measure the amounts of interleukin-1 receptor antagonist (IL-1ra) protein produced by cultured synovial cells obtained from patients with rheumatoid arthritis (RA) and osteoarthritis (OA). METHODS--Synovial cells obtained from patients with either RA or OA were cultured and the supernatants were measured for IL-1ra by enzyme linked immunosorbent assay. RESULTS--The synovial cells obtained from patients with RA produced significantly smaller amounts of IL-1ra than did those obtained from patients with OA, in a late passage (third to fifth) without stimulation and a first passage both with and without stimulation (p < 0.025, respectively). In addition, when the patients with RA were divided into two groups according to the maximum number of lining cell layers, the amounts of IL-1ra produced by the proliferative type were smaller than those produced by the less proliferative type (p < 0.025). CONCLUSIONS--The above findings suggest that IL-1ra production in RA synovial cells is suppressed, and that reduced IL-1ra protein production is one of the causes which leads to the proliferation of lining cells and persistent joint inflammation.